Finite-Time Adaptive Sliding Mode Control of a Power Converter Under Multiple Uncertainties - Amrr , Syed Muhammad; Ahmad , Javed; Waheed , Sofi Abdul; Sarwar , Adil; Saidi , Abdelaziz Salah; Nabi , M. (Frontiers in Energy Research, 2022)
This paper investigates the use of a new sliding mode control for the output voltage regulation of boost converter under parametric uncertainties of load resistance and input voltage. Owing to the fact that the proposed scheme employs the adaptation law; therefore, apriori knowledge about the upper bound value of uncertainties is not required while selecting the controller gains. Moreover, the stability analysis of the closed-loop system guarantees the finite-time convergence of output voltage to the desired value while ensuring robustness against uncertainties. The numerical simulation and hardware analysis illustrate the effective performance of the developed strategy.